Potential Clients’ Purchase Intention of Green Building in Kathmandu Valley - Bhandari, Bindu; Danuwar, Ranjana Kumari; Nepal, Bibek; Shrestha, Purna Man (Khwopa Journal, 2025)
Green building practices have gained global attraction, with developed countries and emerging economies adopting eco-conscious construction. However, Nepal faces challenges in its building sector, lacking a mandatory energy-efficient rating system. This, this study aims to investigate the potential clients purchase intension of green building in Kathmandu Valley. Explanatory research design was used to explore the cause-and-effect relationship among factors influencing Potential Clients' Adoption Preference of Green Buildings in the Kathmandu Valley. Data is collected from 404 potential clients through purposive sampling and structured questionnaires. The Kobo Toolbox administers the data, which is then analyzed using partial least squares structural equation modeling (PLS-SEM) version 4.0 software. Research findings indicated significant relationship of relative advantage and compatibility show significant relationships with green building adoption, while environmental opinion leadership, innovativeness, simplicity, and trialability does not demonstrate significant relationship. The study highlights that respondents were highly aware about the green building. Similarly, respondents had heard about the green building practices through social media platforms, newspapers, publications and article, word of mouth, and radios etc. Furthermore, delving into additional factors such as individual risk preferences and socio-economic influences will provide a more comprehensive understanding of green building adoption.